A novel automated method for the objective quantification of Retinal layers reveals sequential changes that occur in the Normal retina with age. Issue 5 (October 2015) - El-Baz, Shlomit Schaal; ElTanboly, Ahmed; Ismail, Marwa; Switala, Andy; , Ahmed Shalaby; , Amir Hadayer; Ab, Omar
No abstract available